Hallazgos hematológicos en perros y gatos en Lima, Perú - Grandía G., Raiden (2020)
The aim of this study was to conduct a haematological evaluation of dogs and cats in Lima, Peru. A total of 460 blood samples (410 dogs and 50 cats) were collected between December 2017 and May 2018. The smears were stained with Wright and the reticulocytes were stained with Brilliant cresyl blue. Descriptive statistics were performed for quantitative variables in the erythroid, myeloid and lymphoid series, as well as the frequency analysis of qualitative variables between species indicator of type of anaemia and leukaemia, ability of medullary regeneration, abnormal morphological changes, out of physiological range and presence of extra and intracellular microorganisms. The most frequent alterations were normochromic normocytic anaemia (23.2% dog, 10% cat), megaloblastic anaemia (5.1% dog), severe hypochromic microcytic anaemia (4% cat), neutrophilic chronic myeloid leukaemia (7.1% dog, 8% cat), monocytosis with cytoplasmic vacuolization in monocytes (4.9% dog), severe thrombocytosis with platelet aggregates (6% cat), polychromatophilia (6.3% dog), dacrocytes (54.4% dog, 64% cat), acanthocytes (11.7% dog, 40% cat) , macrocytes (14.6% dog, 6% cat), small leukocytes (10% dog, 6% cat), Cytauxzoon felis (20% cat), Anaplasma spp (0.2% dog) and Mycoplasma spp (2% dog, 20% cat). Only significant differences were observed between sexes in total platelets (p=0.0087) and eosinophils (p=0.0260) being greater in male dogs. It is concluded that the prevalence of C. felis in the cats studied is relatively low and there is a risk of zoonosis of Anaplasma spp and Mycoplasma spp in the owners of affected animals in Lima, Perú.